Lepton-pair scattering with an off-shell and an on-shell photon at two loops in massless QED - Simon Badger; Jakub Kryś; Ryan Moodie; Simone Zoia (Journal of High Energy Physics, 2023)
Abstract We compute the two-loop QED helicity amplitudes for the scattering of a lepton pair with an off-shell and an on-shell photon, 0 → ℓ ℓ ¯ γγ $$ \ell \overline{\ell}γ γ $$ *, using the approximation of massless leptons. We express all master integrals relevant for the scattering of four massless particles with a single external off-shell leg up to two loops in a basis of algebraically independent multiple polylogarithm, which guarantees an efficient numerical evaluation and compact analytic representations of the amplitudes. Analytic forms of the amplitudes are reconstructed from numerical evaluations over finite fields. Our results complete the amplitude-level ingredients contributing to the N3LO predictions of electron-muon scattering eμ → eμ, which are required to meet the precision goal of the future MUonE experiment.